Determinantes da repetência escolar no Brasil: Uma análise de painel dos censos escolares entre 2007 e 2010 - Luís Felipe Batista de Oliveira; Sergei S. D. Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper investigates the main determinants of grade repetition using the Brazilian school census between 2007 and 2010. For the first time such a study is conducted with all students in a panel. We begin with a brief analysis of attrition in the school census and then estimate logistic regressions for the probability of non-approval year-by-year. Variables of physical disability, repetition in the previous year and length of the school day are the most important determinants. Finally, we estimate a panel logit considering time effects.
Keywords: I21; C33; C35; 330